2016
DOI: 10.4172/2157-7579.1000379
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasites in the Intestine of Dogs (Sheep-Keeper, Owned, Pet and Stray) in Duhok Province, Kurdistan Region

Abstract: This survey was done to investigate the prevalence of internal parasites in the intestine of dogs in Duhok province from February to October 2015. A total of 270 sheep-keepers, owned, pet and stray dogs' fecal samples from most areas in Duhok province were collected and examined by flotation technique, sedimentation technique and direct smear. During this study Spirocerca lupi (0.7%) and Uncernia stenocephala (2%) were recorded for the first time in Kurdistan region; while Diplydium caninum (16.7%), Strongyloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Through microscopic examinations, the infection rate of G. duodenalis observed in dogs was 14.67%. This result was significantly aligned with a previous study by Hassan [ 17 ] that reported a 16% infection rate in Erbil, which was higher than the rate reported in another study conducted in Duhok Province (5.2%) [ 18 ]. However, the infection rate observed in this study was lower than that recorded in Basrah (75.55%) [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Through microscopic examinations, the infection rate of G. duodenalis observed in dogs was 14.67%. This result was significantly aligned with a previous study by Hassan [ 17 ] that reported a 16% infection rate in Erbil, which was higher than the rate reported in another study conducted in Duhok Province (5.2%) [ 18 ]. However, the infection rate observed in this study was lower than that recorded in Basrah (75.55%) [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed that the infection rate of canine intestinal parasites was comparable to the prevalence that was reported by various other studies in different parts of Iraq (Muhamed and Al-Barwary, 2016;Khawla et al, 2017). The results of this study were agreed with the results of Muhamed and Al-Barwary (2016) who recorded 65.9% in Duhok province and also agree with the results of Khawla et al, (2017) in Basra province, southern Iraq. However, the prevalence results of the present study appeared to be higher than the prevalence report (16.66%) in dogs in Diyala province (Hasson, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Province [16]. It is noteworthy, in the present study the infections with zoonotic GIP s such as T. canis, Stongyloides sp.…”
mentioning
confidence: 55%